2019
DOI: 10.1002/jgc4.1144
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐centered care and genomic medicine: A qualitative provider study in the military health system

Abstract: The diagnostic and predictive information produced by genomic sequencing may impact medical management, and it is critical that providers and institutions are able to use this information appropriately for patient care. Guided by the patient-centered care model, we investigated provider perspectives of patient, provider, and system-level factors that could influence the implementation of genomic medicine within the integrated healthcare system of the US Department of Defense (DOD).The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…In ANOVA and linear regression analysis, there were no significant associations among genetic counselor demographics, their reported self‐efficacy from the GCSES scale, and military knowledge. These results are consistent with a qualitative study by Hellwig, Turner, Manolio, et al (2019) and Hellwig, Turner, and O’Neill (2019) suggesting that providers within the military health system itself had varied knowledge of the military‐specific policies that govern how genetic information is managed within military healthcare.…”
Section: Discussionsupporting
confidence: 89%
“…In ANOVA and linear regression analysis, there were no significant associations among genetic counselor demographics, their reported self‐efficacy from the GCSES scale, and military knowledge. These results are consistent with a qualitative study by Hellwig, Turner, Manolio, et al (2019) and Hellwig, Turner, and O’Neill (2019) suggesting that providers within the military health system itself had varied knowledge of the military‐specific policies that govern how genetic information is managed within military healthcare.…”
Section: Discussionsupporting
confidence: 89%
“…Alharbi et al assessed the knowledge of 126 South Arabian physicians about PM in diabetes mellitus management and found that 82.5% of the participants had poor knowledge in this area [ 82 ]. These and other studies [ 37 , 44 47 , 58 , 86 , 105 108 ] reveal the need for further education of many health care providers, however, this requirement may vary between professionals in different fields [ 53 , 81 ]. An exception seems to be the skills of physicians in oncology.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, representatives from patient organizations note that patients often have difficulties in understanding basic medical information and that patient education will be a major task for patient organizations [ 96 ]. Hellwig et al pointed out that patients’ understanding is also in the interest of health care providers, as it facilitates the communication process [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges and opportunities relevant for visualization in clinical genomics has been discussed in previous work. Handling variants of unknown significance is one such challenge ( Biesecker, 2012 ; Hellwig et al, 2019 ), as is other types of decision support design ( Yaung and Pek, 2021 ; Kulchak Rahm et al, 2021 ). Effective reporting is another area in focus, both to ordering physician and to patients ( Biesecker (2012) ; Wynn et al, 2018 ; Sanderson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%